Mesenchymal Stem Cell Delivery via Topographically Tenoinductive Collagen Biotextile Enhances Regeneration of Segmental Tendon Defects. Issue 8 (July 2022) - McClellan, Phillip; Ina, Jason G.; Knapik, Derrick M.; Isali, Ilaha; Learn, Greg; Valente, Alexis; Wen, Yujing; Wen, Ruiqi; Anderson, James M.; Gillespie, Robert J.; Akkus, Ozan
Background: Successful management of massive rotator cuff (RC) tendon tears represents a treatment challenge because of the limited intrinsic healing capacity of native tendons and the risk of repair failure. Biologic augmentation of massive RC tears utilizing scaffolds—capable of regenerating bulk tendon tissue to achieve a mechanically functional repair—represents an area of increasing clinical interest. Purpose: To investigate the histological and biomechanical outcomes after the use of a novel biologic scaffold fabricated from woven electrochemically aligned collagen (ELAC) threads as a suture-holding, fully load-bearing, defect-bridging scaffold with or without mesenchymal stem cells (MSCs) compared with direct repair in the treatment of critically sized RC defects using a rabbit model. Study Design: Controlled laboratory study. Methods: A total of 34 New Zealand White rabbits underwent iatrogenic creation of a critically sized defect (6 mm) in the infraspinatus tendon of 1 shoulder, with the contralateral shoulder utilized as an intact control. Specimens were divided into 4 groups: (1) gap—negative control without repair; (2) direct repair of the infraspinatus tendon—operative control; (3) tendon repair using ELAC; and (4) tendon repair using ELAC + MSCs. Repair outcomes were assessed at 6 months using micro–computed tomography, biomechanical testing, histology, and immunohistochemistry. Results: Specimens treated with ELAC demonstrated significantly less tendon retraction when compared with the direct repair group specimens ( P = .014). ELAC + MSCs possessed comparable biomechanical strength (178 ± 50 N) to intact control shoulders (199 ± 35 N) ( P = .554). Histological analyses demonstrated abundant, well-aligned de novo collagen around ELAC threads in both the ELAC and the ELAC + MSC shoulders, with ELAC + MSC specimens demonstrating increased ELAC resorption (7% vs 37%, respectively; P = .002). The presence of extracellular matrix components, collagen type I, and tenomodulin, indicating tendon-like tissue formation, was appreciated in both the ELAC and the ELAC + MSC groups. Conclusion: The application of MSCs to ELAC scaffolds improved biomechanical and histological outcomes when compared with direct repair for the treatment of critically sized defects of the RC in a rabbit model. Clinical Relevance: This study demonstrates the feasibility of repairing segmental tendon defects with a load-bearing, collagen biotextile in an animal model, showing the potential applicability of RC repair supplementation using allogeneic stem cells.